The explosive growth of social media: Trump, COVID-19, the Russian invasion of Ukraine, and Elon Musk - Levinson, Paul (Wydawnictwa AGH, 2022)
Social media have arisen to become the world’s go-to mode of communication in an astonishing fifteen years. In the past few years, social media themselves have been shaken by Donald Trump’s use of Twitter, and by deceptive reporting about many crucial aspects of the COVID-19 pandemic. And now, in just the past few months, the Russian invasion of Ukraine has put social media to the test, with an informational war being fought alongside the physical war, and billionaire Elon Musk’s attempt to buy Twitter perhaps ending any attempt to limit deceptive posts that jeopardize human lives. This essay examines what is happening.
Studia Humanistyczne AGH
Keywords: Donald Trump; Elon Musk; Twitter; social media; COVID-19; Russian invasion of Ukraine; media evolution